2011
DOI: 10.1097/mat.0b013e3182246bf8
|View full text |Cite
|
Sign up to set email alerts
|

Central Venous Stenosis Among Hemodialysis Patients is Often Not Associated With Previous Central Venous Catheters

Abstract: It is widely assumed that central venous stenosis (CVS) is most commonly associated with previous central venous catheterization among the chronic hemodialysis (HD) patients. We evaluated the validity of this assumption in this retrospective study. The clinical records from 2,856 consecutive HD patients with vascular access failure during a 5-year period were reviewed, and a total of 26 patients with symptomatic CVS were identified. Combined with radiological findings, their clinical characteristics were exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 24 publications
2
39
2
1
Order By: Relevance
“…Flossing guidewire technology has the advantage of offering sufficient propulsion and steering force, which is the major reason why endovascular treatment has been widely used in recent years. For example, the flossing guidewire technique is efficient and useful to guide the stent through the places of extreme bending, such as the aortic arch in aortic dissection, usually referred to as the "Gothic arch" [3, 33–35]. The “Gothic arch” also exists in the central venous structures.…”
Section: Discussionmentioning
confidence: 99%
“…Flossing guidewire technology has the advantage of offering sufficient propulsion and steering force, which is the major reason why endovascular treatment has been widely used in recent years. For example, the flossing guidewire technique is efficient and useful to guide the stent through the places of extreme bending, such as the aortic arch in aortic dissection, usually referred to as the "Gothic arch" [3, 33–35]. The “Gothic arch” also exists in the central venous structures.…”
Section: Discussionmentioning
confidence: 99%
“…Although a wide range of pathogenesis including the positioning and size of muscles, ligaments, bones, and vessels that surround the central veins, may contribute to the development of CVS [1][2][3][4][5][6][7], information about their impact on the development of CVS among HD patients is still poorly understood. Nevertheless, we propose the concept that the combination of various degree of chronic venous compression at the level of thoracic outlet characterized by the natural physique and elevated venous flow induced by the creation of vascular access should be evaluated as a potential factor for the development of CVS, since there might be a continuum in the relationship between the degree of the thoracic outlet venous compression and subclavian venous susceptibility to CVS presumably through the stimulation of intimal hyperplasia.…”
Section: Presentation Of the Hypothesismentioning
confidence: 99%
“…However, CVS may also develop without a history of central venous catheterization. Indeed, a recent study of chronic HD patients with symptomatic CVS demonstrated the number of patients without a history of central venous catheterization to be greater than those who had undergone a previous cannulation, thus suggesting that cases without a previous history of central venous catheterization may not necessarily be rare among such patients [3]. Mechanical injury from either catheter insertion or continuous catheter movement inside the vasculature, thereby invoking endothelial damage, neointimal hyperplasia, and fibrosis seems to play a role in the development of CVS among the patients with a previous history of central venous catheterization [1,2], while vascular access-related changes in the arterialized flow dynamics leading to abnormal shear stress, turbulence, platelet aggregation, may also act as an basic determinant for the development of CVS among chronic HD patients regardless of the previous history of central venous catheterization [4][5][6][7].…”
Section: Introductionmentioning
confidence: 96%
“…Although recent studies indicate extrinsic compression of LIV by adjacent anatomical structures, such as the aortic arch, innominate artery and sternum may be another mechanism for LIV stenosis [57]. However, most of these studies are focusing on hemodialysis patients with clinical symptoms compatible with LIV stenosis, including arm edema, arm ulceration, ipsilateral face swelling, visible collateral veins, and venous dilatation [79]. For example, KOTODA et al reported that LIV stenosis occurred in seven hemodialysis patients using digital subtraction angiography (DSA) and confirmed an anatomic relationship among the LIV, sternum, and arch vessels by multi-detector computed tomography (MDCT) angiography [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these studies are focusing on hemodialysis patients with clinical symptoms compatible with LIV stenosis, including arm edema, arm ulceration, ipsilateral face swelling, visible collateral veins, and venous dilatation [79]. For example, KOTODA et al reported that LIV stenosis occurred in seven hemodialysis patients using digital subtraction angiography (DSA) and confirmed an anatomic relationship among the LIV, sternum, and arch vessels by multi-detector computed tomography (MDCT) angiography [9]. Further, Shi et al [8] proved that these anatomical factors to contribute to LIV stenosis in hemodialysis patients by measuring the LIV diameter as well as the space between the sternum and aortic arch on the cross section of the MDCT scan.…”
Section: Introductionmentioning
confidence: 99%